Power quality improvement in distribution systems considering Optimum D-STATCOM placement - Farhoodnea, Masoud; Azah Mohamed,; Hussain Shareef,; Zayandehroodi, Hadi (Fakulti Kejuruteraan ,UKM,Bangi., 2013)
This paper presents an improved method in solving the optimization problem related to the optimum placement and sizing of the Distribution Static Synchronous Compensator (D-STATCOM) in distribution systems, which use the firefly algorithm (FA) for power quality improvement. In the proposed method, the voltage total harmonic distortion, voltage deviation, and total investment cost indices are considered as the problem sub-objective functions. The voltage and power limits for individual buses are considered as the constraints to control optimization variables. The proposed FA is implemented using the Matlab software on modified IEEE 16- and 34-bus test systems. The obtained results are compared with the particle swarm optimization and the genetic algorithm. The simulation and comparison results verify the ability of the FA to accurately determine the optimal location and size of the D-STATCOM in radial distribution systems.